Snorkelers’ Perceptions toward Coral Bleaching at Tarutao National Park, Satun Province - Akase, Kentaro; Emphandhu, Dachanee; Wongwathana Foster, Phatchanuch (วารสารวนศาสตร์ไทย, 2022)
The coral bleaching in 2010 has led to substantial coral mortality in Tarutao National Park. This phenomenon affects the well-being of coral and its associated marine life, and can potentially harm marine tourism activities in the park, particularly snorkeling and scuba diving. The main objectives of this research were to investigate snorkelers’ perception on coral bleaching and their satisfaction level as a result of snorkeling in the park. 322 on-site snorkelers were interviewed through the structured questionnaire. The data was analyzed using descriptive statistics, chi-square and t-test. The results revealed that most snorkelers (56.2%) did not realize that the park had experienced coral bleaching. A similar number of snorkelers (55.9%) responded that the closure of snorkeling sites did not affect their decision to visit the park, and a majority of them (68.9%) never noticed any coral bleaching while snorkeling. For hypothesis testing, three factors, namely nationality, perceived information, and coral bleaching knowledge were found to be significantly correlated to snorkelers’ perception on physical appearance of coral bleaching. It was also found that coral bleaching moderately affected snorkelers’ experience or satisfaction as they expressed their willingness to visit the park again in the future. Moreover, the hypothesis testing revealed that snorkeling satisfaction did not correlate to both of coral bleaching observed and information perceived on coral bleaching situation. The overall findings of this study implied that coral bleaching has no significant impact on snorkelers and their satisfaction. The long-term viability of marine tourism in the park could rest on high quality of other park resources and environment besides coral reef such as clean beaches, clear sea water, seascape and other esthetic values. Keywords: Snorkeler, Perception, Coral Bleaching, Tarutao National Park